Capnography as an aid in localizing the phrenic nerve in brachial plexus surgery. Technical note - Bhagat, Hemant; Agarwal, Anil; Sharma, Manish S (Journal of Brachial Plexus and Peripheral Nerve Injury, 2008)
Background To determine whether monitoring end- tidal Carbon Dioxide (capnography) can be used to reliably identify the phrenic nerve during the supraclavicular exploration for brachial plexus injury.Methods Three consecutive patients with traction pan-brachial plexus injuries scheduled for neurotization were evaluated under an anesthetic protocol to allow intraoperative electrophysiology. Muscle relaxants were avoided, anaesthesia was induced with propofol and fentanyl and the airway was secured with an appropriate sized laryngeal mask airway. Routine monitoring included heart rate, noninvasive blood pressure, pulse oximetry and time capnography. The phrenic nerve was identified after blind bipolar electrical stimulation using a handheld bipolar nerve stimulator set at 2–4 mA. The capnographic wave form was observed by the neuroanesthetist and simultaneous diaphragmatic contraction was assessed by the surgical assistant. Both observers were blinded as to when the bipolar stimulating electrode was actually in use.Results In all patients, the capnographic wave form revealed a notch at a stimulating amplitude of about 2–4 mA. This became progressively jagged with increasing current till diaphragmatic contraction could be palpated by the blinded surgical assistant at about 6–7 mA.Conclusion Capnography is a sensitive intraoperative test for localizing the phrenic nerve during the supraclavicular approach to the brachial plexus.